Co-designing a dementia-specific education and training program for home care workers: The 'Promoting Independence Through Quality Dementia Care at Home' project. (April 2022) - Goh, Anita MY; Doyle, Colleen; Gaffy, Ellen; Batchelor, Frances; Polacsek, Meg; Savvas, Steven; Malta, Sue; Ames, David; Winbolt, Margaret; Panayiotou, Anita; Loi, Samantha M; Cooper, Claudia; et al.
Undertaking co-design with the end users of services has rapidly evolved as the best-practice approach to program design, development and implementation. Increased interest in using participatory co-design in dementia care has drawn attention to the need for evidence-informed methods for facilitating the meaningful involvement of people with dementia and their family carers in co-design activities. The aim of this paper is to describe the co-design framework used in the co-design of a dementia specialist training program for home care workers. The Promoting Independence Through quality dementia Care at Home program is a successful example of co-design methodology used across multiple project stages and with various stakeholder groups, including people living with dementia, family carers, home care workers, managers and researchers. Co-design methods were tailored to each stage, purpose, and stakeholder group, and to facilitate the involvement of people living with dementia. Findings provide unique insights into optimising input from co-design partners, including people living with dementia; the methodology, conditions and requirements for participants to co-design and implement ideas; and perspectives on the enablers and challenges of using co-design in this population. In this paper, we present a comprehensive approach for involving people living with dementia as active and equal contributors in inclusive and meaningful participatory co-design.